ChemInform Abstract: Catalytic Efficiency of Primary β‐Amino Alcohols and Their Derivatives in Organocatalysis. Issue 42 (September 2016) - Reddy, Ummareddy Venkata Subba; Chennapuram, Madhu; Seki, Chigusa; Kwon, Eunsang; Okuyama, Yuko; Nakano, Hiroto
Abstract: Review: [81 refs.